A joint electromagnetic and seismic study of an active pockmark within the hydrate stability field at the Vestnesa Ridge, West Svalbard margin. Issue 10 (31st October 2015) - Goswami, Bedanta K.; Weitemeyer, Karen A.; Minshull, Timothy A.; Sinha, Martin C.; Westbrook, Graham K.; Chabert, Anne; Henstock, Timothy J.; Ker, Stephan
Abstract: We acquired coincident marine controlled source electromagnetic (CSEM), high‐resolution seismic reflection and ocean‐bottom seismometer (OBS) data over an active pockmark in the crest of the southern part of the Vestnesa Ridge, to estimate fluid composition within an underlying fluid‐migration chimney. Synthetic model studies suggest resistivity obtained from CSEM data can resolve gas or hydrate saturation greater than 5% within the chimney. Acoustic chimneys imaged by seismic reflection data beneath the pockmark and on the ridge flanks were found to be associated with high‐resistivity anomalies (+2–4 Ωm). High‐velocity anomalies (+0.3 km/s), within the gas‐hydrate stability zone (GHSZ) and low‐velocity anomalies (−0.2 km/s) underlying the GHSZ, were also observed. Joint analysis of the resistivity and velocity anomaly indicates pore saturation of up to 52% hydrate with 28% free gas, or up to 73% hydrate with 4% free gas, within the chimney beneath the pockmark assuming a nonuniform and uniform fluid distribution, respectively. Similarly, we estimate up to 30% hydrate with 4% free gas or 30% hydrate with 2% free gas within the pore space of the GHSZ outside the central chimney assuming a nonuniform and uniform fluid distribution, respectively. High levels of free‐gas saturation in the top part of the chimney are consistent with episodic gas venting from the pockmark. Key Points: First joint CSEM and seismic analysis of an active pockmark at Vestnesa ridge Synthetic resistivity models suggested sensitivity to underlying chimney Estimated a gas‐ and hydrate‐saturated chimney beneath pockmark supports venting